Proceedings of the 17th Conference on Pattern Languages of Programs 2010
DOI: 10.1145/2493288.2493310
|View full text |Cite
|
Sign up to set email alerts
|

Sharing bad practices in design to improve the use of patterns

Abstract: In order to guarantee the use of good analysis and design practices and an easier maintenance of software, analysts and designers may use patterns. To help them, we propose models inspection in order to detect instantiations of "spoiled pattern" and models reworking through the use of the design patterns. As a design pattern allows the instantiation of the best known solution for a given problem, a "spoiled pattern" allows the instantiation of alternative solutions for the same problem: requirements are respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…Although this systematic review did not find studies focused on the co-occurrence of design patterns and bad smells, there are reported cases in the software engineering literature where the use of design patterns may not always be the best option [19] [25]. In general, we tend to think that if developers employ cataloged design patterns [4], then hypothetically the best solution to solve the problem has been used [2] and the best practices are been employed. However, this thought is not necessarily true since a design pattern may be misused or even overused.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this systematic review did not find studies focused on the co-occurrence of design patterns and bad smells, there are reported cases in the software engineering literature where the use of design patterns may not always be the best option [19] [25]. In general, we tend to think that if developers employ cataloged design patterns [4], then hypothetically the best solution to solve the problem has been used [2] and the best practices are been employed. However, this thought is not necessarily true since a design pattern may be misused or even overused.…”
Section: Related Workmentioning
confidence: 99%
“…Among these, some tools [3] [7][15] [17] have been proposed to identify code fragments that can be refactored to patterns. Other studies [2][6] establish a structural relationship between the terms design pattern and bad smell. In addition, there are reported cases in the literature where the use of design patterns may not always be the best option and the wrong use of a design pattern can even introduce bad smells in code [19] [25].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a spoiled pattern does not bring the same design qualities and this may frequently introduce design defects. As it is often useful to correct these local design defects, we suggest to detect (Bouhours et al 2010) and correct alternative solutions with a tooled design review activity (Bouhours et al 2009(Bouhours et al , 2011. The aim is to inspect models to search for fragments which are characteristic of the use of spoiled patterns and to substitute solutions using design patterns for them.…”
Section: (A) (B)mentioning
confidence: 99%
“…For instance, studies [18][19][20] proposed tools that suggest fragments need refactoring. Other studies [21,22] investigated the relation between design patterns and code smells in terms of their structural relationship. Furthermore, Wendorff [9] reported cases where design patterns may have negative impact on attributes like maintainability which may lead to introduce bad smells.…”
Section: Introductionmentioning
confidence: 99%